EFEKTIVITAS KULIT BAWANG MERAH (Allium ascalonicum) TERHADAP PERTUMBUHAN PAKCOY (Brassica rapa) - Yosi Dwi Ananda Putri; Surti Kurniasih; . Munarti (EKOLOGIA, 2021)
Mustard production in indonesia from 2017 to 2019 had been decreasing year by year, while market demanded for vegetable production had increased.  On the other handed, shallot production in 2017 to 2019 increased, resulting in an abundance of shallot waste.  Natural resources in the form of organic materials and organic waste that exist around farmers and the community in general could been made as organic fertilizer.  Based on this, it was necessary to studied the effectiveness of liquid organic fertilizer (poc) of onion peel waste on the growth of pakcoy plants.  The purpose of this studied was to studied the effect of onion peel waste on the growth of pakcoy.  This studied used an experimental method with a completely randomized design (crd) consisting of 5 treatments and each treatment consisted of 5 replications, so the total number of experimental units was 25 experimental units.  The concentration given to each treatment was p0 (0%), p1 ( 20%), p2 (40%), p3 (60%) and p4 (80%).  Growth parameters observed was number of left, plant height and wet weight.  The results showed that the administration of red onion peel waste had a significant effect on the growth of pakcoy on the three parameters observed.  The optimal treatment for the number of left was p1(20%), plant height p3 (60%) and wet weight p1(20%) Keywords: Liquid Organic Fertilizer, Pakcoy, Shallots